Hidrogenasi Hidrotermal Katalitik Asam Oleat dengan Produksi Hidrogen secara in-situ Menggunakan Katalis NiO/y-Al2O3 - Nainggolan, Federiko Markus Lasardo; Tirto Prakoso; Meiti Pratiwi (Fakultas Teknik - Universitas Jenderal Achmad Yani, 2023)
Hydrogenation reaction is one of the most important reactions for the oleochemical industry to convert unsaturated fatty acids into saturated fatty acids and their derivatives. The need for large amounts of hydrogen in hydrogenation reactions will be a problem in terms of hydrogen availability and economy. Catalytic hydrothermal technology offers several advantages including the ability to produce hydrogen in-situ. The focus of this research is to evaluate the effect of metal charge addition on the catalyst, the effect of tin addition on NiO/y-Al2O3 catalyst and the effect of glycerol addition as a source of H2 production in-situ on the hydrogenation conversion of oleic acid. The catalyst was prepared by dry impregnation method. XRD, XRF and BET characterization of the catalysts confirmed the presence of Ni and Sn metals on the catalysts. Hydrogenation conversion in the reaction without glycerol using NiO/y-Al2O3 catalyst at 300oC for 6 hours did not show significant changes with the addition of metal loading. However, the addition of Sn metal increased the selectivity of in-situ H2 production used to hydrogenate oleic acid with a hydrogenation conversion of 36%. The addition of glycerol to the reactants also increased the hydrogenation conversion compared to the reaction without glycerol.